2018
DOI: 10.1002/ghg.1763
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Cu–Fe‐based oxygen carrier combined with a Ni‐based oxygen carrier in a chemical‐looping combustion process based on fixed‐bed reactors

Abstract: The application of chemical‐looping combustion (CLC) based on fixed‐bed reactors for distributed medium‐ and small‐scale hot‐water and steam gas‐fuelled boilers is promising due to its low NOx emission, high energy efficiency and nearly zero energy consumption in carbon capture. For fixed‐bed reactors, a wide operating temperature window (Tw) for the oxygen carrier (OC) is crucial to ensure the performance and cycle life of the OC. The performance of Cu30–Fe50/Al20‐M combined with different Ni‐based OCs was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The authors believe that this improvement results from more efficient gas-solid mass transfer due to the reduced bubble size. Detailed results from experimental tests on fixed bed reactors are reported in [105][106][107][108][109][110].…”
Section: Swing Reactormentioning
confidence: 99%
“…The authors believe that this improvement results from more efficient gas-solid mass transfer due to the reduced bubble size. Detailed results from experimental tests on fixed bed reactors are reported in [105][106][107][108][109][110].…”
Section: Swing Reactormentioning
confidence: 99%
“…It was also found that the introduction of a NiO-based oxygen carrier into the Fe 2 O 3 /CuO-based oxygen carrier bed facilitated the reduction of the operating temperature in CLC process, due to the high reactivity of Ni towards CH 4 . Further, a layer-by-layer mixing mode of a NiO-based oxygen carrier and a Fe 2 O 3 /CuO-based oxygen carrier in a fixed-bed reactor avoids the formation of NiFe 2 O 4 spinel during the reduction half-cycle, ensuring a good redox rate, thereby providing a promising reactor configuration candidate for an enhanced-CH 4 -reforming chemical looping process [132]. …”
Section: Improvements To Oxygen Carriersmentioning
confidence: 99%